ANALISIS PERKEMBANGAN PROSES PEMBELAJARAN DI SEKOLAH DASAR (SD) DENGAN BERBAGAI MEDIA PEMBELAJARAN SESUAI KURIKULUM YANG TERUS BERGANTI - Dwi Putri Janrida Sianturi, Rasyah Theresia Tampubolon, Fiber Yun Almanda Ginting (CV. ADIBA AISHA AMIRA, 2024)
This research discusses the direction of curriculum policy in elementary schools (SD) with various learning media that are in accordance with the curriculum. The independent curriculum is a new curriculum implemented in Indonesia in 2022. This curriculum gives teachers and students the freedom to learn and teach more creatively and innovatively. This research uses a qualitative method based on literature study. Data is collected from various sources such as books, scientific journals, and websites. The results of the research show that the direction of the independent curriculum policy in elementary schools is focused on several things, namely: Development of students' core competencies, contextual and problem-based learning, authentic assessment, character and ethics development, parent participation in learning. Various efforts continue to be made, but it is impossible to cover up the existing problems. Several problems experienced by teachers or schools in implementing the independent learning curriculum have become new challenges for teachers in teaching.